Physical mapping of 35S rRNA genes and genome size variation in polyploid series of Sisyrinchium micranthum and S. rosulatum (Iridaceae: Iridoideae). (4th May 2017) - Tacuatiá, L. O.; Kaltchuk-Santos, E.; Souza-Chies, T. T.; Eggers, L.; Forni-Martins, E. R.; Pustahija, F.; Robin, O.; Siljak-Yakovlev, S.
Abstract: Sisyrinchium micranthum and S. rosulatum are part of a species complex in which S. micranthum displays considerable morphological variation. S. rosulatum is a tetraploid species, whereas S. micranthum plants may present three different ploidy levels (2 x, 4 x, and 6 x ), so that polyploidy might have an important role in the diversification of this group. Notwithstanding, most cytogenetic studies on these species are based on chromosome counting. Aiming to understand how polyploidy may have impacted the genomes of these species, the DNA content of 184 specimens was estimated; fluorochrome banding with chromomycin A3 and fluorescent in situ hybridization using an 18S-5.8S-26S ribosomal DNA (rDNA) probe were also performed . The results showed a reduction in monoploid genome size (1Cx), as well as in the number of heterochromatin bands and rDNA sites per monoploid genome, from diploids to polyploids. Additionally, intraspecific and within-ploidy variations in genome size and number of rDNA sites were observed. The source of varying structure in genome organization of these plants may be the multiple independent formations of polyploids along with an ongoing diploidization process. However, the intraspecific and within-ploidy polymorphisms indicate genetic mechanisms other than genome duplication and diploidization to be important to the genome evolution of these taxa.